2003
DOI: 10.1104/pp.102.019851
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Properties of Rice and the Response of Gas Exchange to Water Stress

Abstract: We investigated the role of xylem cavitation, plant hydraulic conductance, and root pressure in the response of rice (Oryza sativa) gas exchange to water stress. In the field (Philippines), the percentage loss of xylem conductivity (PLC) from cavitation exceeded 60% in leaves even in watered controls. The PLC versus leaf water potential relationship indicated diurnal refilling of cavitated xylem. The leaf water potential causing 50 PLC (P 50 ) was Ϫ1.6 MPa and did not differ between upland versus lowland rice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
103
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(114 citation statements)
references
References 52 publications
3
103
4
1
Order By: Relevance
“…With daily C min being 0.3 to 1.4 MPa lower than P k50 , at least two of our species would incur significant water transport reduction during the course of the day (Tables I and II; Stiller et al, 2003), limiting transpiration and, thus, according to Ohm's law, preventing a further decrease of C. However, the staining experiment suggests that embolism plays only a minor role in hydraulic decline at the observed in situ C (Fig. 2); therefore, water transport is limited mainly by reversible extraxylary effects (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…With daily C min being 0.3 to 1.4 MPa lower than P k50 , at least two of our species would incur significant water transport reduction during the course of the day (Tables I and II; Stiller et al, 2003), limiting transpiration and, thus, according to Ohm's law, preventing a further decrease of C. However, the staining experiment suggests that embolism plays only a minor role in hydraulic decline at the observed in situ C (Fig. 2); therefore, water transport is limited mainly by reversible extraxylary effects (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…4). This apparent increase in Ψ L may be partially explained by the findings of Stiller et al (2003), who showed that even at -2 MPa, rice roots were vulnerable to cavitation, with xylem conductivity in leaves dropping by as much as 90%. Nevertheless, the plants were able to refill cavitated xylem conduits and restore lost xylem hydraulic conductance.…”
Section: Initial Changes In Leaf Water Potentialmentioning
confidence: 92%
“…They concluded that a plant with excised roots could supply the shoot with suffi cient water for it to survive by way of its remaining xylem vessels embolizing less frequently or refilling more quickly, so that the remaining root was more effi cient. Stiller et al (2003) also observed this ability in rice to refill cavitated xylem conduits and restore lost xylem hydraulic conductance. They also noted that reduction in hydraulic conductance could have come from cavitation in roots and stems and soil drying.…”
Section: Subsequent Changes In Leaf Water Potential After Root Severingmentioning
confidence: 93%
“…Whole plant hydraulic conductivity and individual conductance components are considered the main factors that control the movement of water through the soil-plant system and have been linked with plant transpiration and other physiological processes related with transpiration [126][127][128][129]. Differences in root hydraulic conductance may cause differences in water transport from soil to plant, influencing the leaf water status and therefore in the growth and other physiological responses of the plant [130].…”
Section: Effects Of Salinity On Leaf Water Relations and Gas Exchangementioning
confidence: 99%